Solar water heating system and photovoltaic floating cover to reduce evaporation: Experimental results and modeling. (May 2017) - Taboada, M.E.; Cáceres, L.; Graber, T.A.; Galleguillos, H.R.; Cabeza, L.F.; Rojas, R.
Abstract: The arid conditions in northern Chile restrict the access to water and energy. This work describes the experimental behavior of a solar water heating system combined with floating covers and photovoltaic cells. Two similar ponds were used for holding water, one heated and the other unheated. The heated pond featured a coil containing an enclosed circulating fluid heated by solar heat collectors. To minimize water evaporation the exposed surfaces of the two ponds were covered by floating elements with photovoltaic cells on top to supply energy for water pumping and to power auxiliary devices of the system. Predicted daily average water temperature values determined from a heat and mass transfer model using experimental meteorological data over eight months of continuous operation were in very good agreement with measured data. The pond with floating covers water evaporation reduction was greater than 90% with respect to an uncovered pond. Also the photovoltaic cells placed on the floating cover generated up to 68 Wp/m 2 equivalent to electric power. The global average for the daily water solar heating that was measured in the pond was equivalent to 420 kWH/m 2 . Highlights: An experimental study on a novel system solar water heating system is described. Water evaporation reduction was achieved through floating modules. Photovoltaic cells mounted on floating modules can be used in small copper processing plants at remote locations. Meteorological data over eight months of continuous operation were in very good agreement with measured data.